Repeat use of contraceptive crisis services among adolescent women. Issue 1 (1st January 2001) - Meyrick, Jane
Abstract : "They don't get pregnant twice unless they are hopeless." This was one Doctor's reported assessment of women who had more than one abortion. There is some evidence that the repeated use of pregnancy testing 'scares', emergency contraception and abortion is increasing across all women. However, there may also be an interaction between this general trend and the difficulties faced by particularly vulnerable groups of teenagers who also have higher rates of teenage parenthood. This paper aims to provide an overview of the research and international statistics in this sparsely researched area. It will draw on the author's own qualitative work with 'high risking' teenage girls, and that of other researchers, in order to attempt to reach an understanding of the mechanisms behind this increasingly common phenomenon. The indications from this work refutes the notion that these women form a special or 'hopeless' group, but point towards general problems with contraception and services common to all women that may become compounded through structural vulnerability such as deprivation.